Surface Modification of Abaca Fibers with Glutaraldehyde for Improved Mechanical Properties of Injection Molded PLA Biocomposites - Harsanti, Dini; Novriadi, Dwi; Pratama, Ade (Journal of Fibers and Polymer Composites, 2024)
This research is based on the importance of finding crosslinking agents that are environmentally friendly and able to improve the performance of the interfacial area between natural fibers and their polymer matrix. Poly(lactic acid) PLA composites containing 20 wt.% abaca (Musa Textilis) fibers were manufactured by injection molding. The composite specimens contained surface-modified abaca fibers with 5 wt.% glutaraldehyde (GA) as a cross-linking agent were examined in this experiment. The SEM was applied to assess the morphological surface of the abaca fibers, while FTIR analysis was performed to investigate the chemical components of abaca fibers. The mechanical characteristics of the PLA/Abaca fiber biocomposites were examined using flexural, tensile, and Izod impact tests. The results confirmed that the modulus of elasticity and Young’s modulus were observed to increase by 40% and 37% respectively. Meanwhile the tensile strength and the flexural strength increased by 26% and 15% respectively. PLA/Abaca fiber biocomposite that had been treated with glutaraldehyde had better mechanical qualities than pure PLA biocomposite.